FEWER KNOTS IN CIRCUMCISION ARE ASSOCIATED WITH LESS POSTOPERATIVE PAIN: A RETROSPECTIVE COMPARATIVE STUDY - Сулейман Сагір; Мустафа Азізоглу; Мюслюм Ергюн (Bukovynian State Medical University, 2023)
Male circumcision is the most frequently performed surgical procedure among Muslim and Jewish communities, mainly for medical, religious, and traditional reasons (1-4). In the USA, circumcision is frequently performed for cosmetic purposes. Although it is seen as a simple procedure, it is quite prone to complications like other surgical procedures. The early and long-term complications of circumcision are well known and the overall complication rate has been reported between 0.2% and 3.9%. Common complications associated with circumcision are acute bleeding, pain, edema, wound infection, and unnecessary foreskin. Rare complications include meatal stenosis, urethral fistula, partial and total glandular amputations, glandular necrosis, penile curvature, and penile rotation. In addition, keloid formation and scar hypertrophy are some rare complications that cause poor cosmetic appearance. The aim of paper: Our aim in this study was to investigate the effect of the number of sutures placed during circumcision on postoperative pain, infection, bleeding amount, and analgesic need in children. Materials and methods: A total of 715 patients who applied to our hospital for circumcision requests between November 2019 and January 2022 were retrospectively analyzed. The patients were randomly divided into three groups according to the number of knots used during the surgical procedure: Group 1 (8 sutures), group 2 (6 sutures), and group 3 (4 sutures). The patients were evaluated in terms of whether they needed analgesics in the postoperative period (1-hour), bleeding status, and whether this bleeding needed re-intervention. Results: The average age of the participants in the study was 4.06±2.51 years, and the average weight was 18.66±7.07 kg. The operation was completed using 8 sutures (group 1) in 47.5%, 6 sutures (group 2) in 27.7%, and 4 sutures (group 3) in 24.9% of the patients. Postoperative infection developed in 2.8% of the participants, and bleeding was observed in 25.1%. The number of participants who needed analgesia for the first hour after the operation was 66.8%. The median value of the postoperative pain scale was 5 (range: 1-9), and those with a pain scale of 5-9 were 65.5%. There was no significant difference between the groups in terms of age, weight, development of infection, and bleeding (p>0.05). Analgesia was needed in 88.7% of those in group 1, 69.9% of those in group 2, and 21.6% of those in group 3 (p<0.001). A score (MPOS) of 5 or higher was found in 86.8% of those in group 1, 71% of those in group 2, and 18.6% of those in group 3 (p<0.001). Conclusions: our study showed that group 3 (4 sutures) achieved lower pain scores, less analgesic consumption, and lower agitation scores after circumcision compared to other groups.